Vowel Hiatus Resolution Processes as Delimiters of Prosodic Domains in Kisa. - Ondondo, Emily Ayieta (Scientific Publishing Group., 2020)
In a language, certain phenomena are sensitive to specific prosodic domains. In a model of morphology-syntax-phonology interaction in which morphological and syntactic structure projects phonological domains belonging to a set hierarchy, each phonological process refers to a specific level of that hierarchy. Therefore, describing a phonological process generally requires specifying the domain within which it applies. In Kisa, a Bantu language spoken in Western Kenya, a sequence of two vowels with different qualities is unacceptable. The ill-formed sequence is repaired through at least one of the vowel processes: gliding, coalescence, raising, assimilation and deletion. These vowel processes involve vowels occurring at different morphological and syntactic boundaries and apply within different prosodic domains in Kisa. Using a qualitative descriptive design and basing on data generated by the author as a native speaker of Kisa, this study identifies and describes the boundaries at which and the prosodic domains in which the vowel processes stated above apply. The findings show that unacceptable vowel sequences occur both at morphological and syntactic boundaries in Kisa. The strategies used to repair the unwanted vowel sequences at each boundary differ depending on the combining vowels. Further, the findings of the study show that the vowel processes attested in the language apply in different domains.
Keywords: Kisa.; Vowel Hiatus Resolution.; Prosodic Domain.; Morphological-Syntactic Boundary.; Gliding; Coalescence.; Assimilation.; Deletion.